If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 23 = 15x + -58 Reorder the terms: 23 + 6x = 15x + -58 Reorder the terms: 23 + 6x = -58 + 15x Solving 23 + 6x = -58 + 15x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-15x' to each side of the equation. 23 + 6x + -15x = -58 + 15x + -15x Combine like terms: 6x + -15x = -9x 23 + -9x = -58 + 15x + -15x Combine like terms: 15x + -15x = 0 23 + -9x = -58 + 0 23 + -9x = -58 Add '-23' to each side of the equation. 23 + -23 + -9x = -58 + -23 Combine like terms: 23 + -23 = 0 0 + -9x = -58 + -23 -9x = -58 + -23 Combine like terms: -58 + -23 = -81 -9x = -81 Divide each side by '-9'. x = 9 Simplifying x = 9
| -x+2=5x+9 | | 6x^2-25x+4=0 | | 3x-3=1x-24 | | 6x-28=20 | | -3(x+4)+6=5(x+3)+1 | | 7(4x+3)+2x-4=-42 | | 8x-11=4x+5 | | 20u-30=9u+3 | | x^2-15x+14=0 | | 9-6x=-7x+21 | | 0.5x-0.7(5-x)=1.9 | | 3-6(1+n)-9=-31 | | 4p^2+8p=0 | | -19x=209 | | 4x-6(7-x)=19 | | 5(-4n+5)-4n=19 | | 3x+4xy-xy=0 | | -6x-4y=-8 | | -32=2(4+6x)-3 | | a+2b-5a-(-b)=0 | | 14(x-5)=-7-7 | | -32=2(4+6)-3 | | x+3y=8 | | 10t=-26 | | 2(x+5)=22 | | 4a-a+3a=0 | | -4x+9x-3=-13 | | 6x-3y-5x+3y= | | 5x-a=2ax+7 | | 16-10x=21-2x | | 3x^2-5x+5=0 | | 6x+5=7x+16 |